Crouch Gait in Dravet Syndrome - Laura Black; Deborah Gaebler-Spira (Pediatric Neurology Briefs, 2016)
Investigators from Necker Enfants Malades Hospital, Sorbonne Paris Cite University, Raymond Poincare University, and Paris Descartes University studied motor neuron function in children with Dravet syndrome (DS).